EVALUASI KEPATUHAN DEBITUR DALAM PENYAMPAIAN PEMBAYARAN PIUTANG PADA PT ALYA PROPERTY TANGERANG SELATAN - Rahayu Rahayu (Universitas Prof. Dr. Moestopo (Beragama), 2022)
PT. Alya Property is located in South Tangerang, engaged in property services, property sold on credit. The problem that arises is that debtors are not orderly in paying installments of receivables, causing bad credit. This dragged on and resulted in the company experiencing difficulties in its operations. To answer this hypothesis, the researchers focused on debtor compliance in the delivery of receivable payments at PT Alya property. he results of the study to answer the hypothesis, then, the analysis of the aging list of accounts receivable can be carried out by PT ALya Property with the presence of an Internal control department in charge of controlling the management of receivables starting from credit sales orders, credit installments to repayment of receivables.